Education and Citizenship: Necessary Contributions for Professional Integration (Interdisciplinary Studies Journal, 2021)
The objective is to reflect on the role of Social Work in Brazilian basic education, with an emphasis on strengthening the professional category in this socio-occupational space. It is the result of a study conducted in light of the historical materialist and dialectical method, using documentary and bibliographic research based on official documents from the representative bodies of the professional category. Citizen education is presented as an education model, considering that it values critical thinking, whose principles govern democracy, and respects differences and freedom. It is highlighted as a historical necessity for the recognition of Social Work’s insertion in basic education.
Keywords: Social Work; Education; Citizenship